Right ventricular outflow tract high-density endocardial unipolar voltage mapping in patients with Brugada syndrome: evidence for electroanatomical abnormalities. Issue Volume 20:Issue FI 1(2018) (2nd May 2017) - Letsas, Konstantinos P; Efremidis, Michael; Vlachos, Konstantinos; Georgopoulos, Stamatis; Karamichalakis, Nikolaos; Asvestas, Dimitrios; Valkanas, Kosmas; Korantzopoulos, Panagiotis; Liu, Tong; Sideris, Antonios
Abstract: Aims: Epicardial structural abnormalities at the right ventricular outflow tract (RVOT) may provide the arrhythmia substrate in Brugada syndrome (BrS). Electroanatomical endocardial unipolar voltage mapping is an emerging tool that accurately identifies epicardial abnormalities in different clinical settings. This study investigated whether endocardial unipolar voltage mapping of the RVOT detects electroanatomical abnormalities in patients with BrS. Methods and results: Ten asymptomatic patients (8 males, 34.5 ± 11.2 years) with spontaneous type 1 ECG pattern of BrS and negative late gadolinium enhancement-cardiac magnetic resonance imaging (LGE-c-MRI) underwent high-density endocardial electroanatomical mapping (>800 points). Using a cut-off of 1 mV and 4 mV for normal bipolar and unipolar voltage, respectively, derived from 20 control patients without structural heart disease established by LGE-c-MRI, the extend of low-voltage areas within the RVOT was estimated using a specific calculation software. The mean RVOT area presenting low-voltage bipolar signals in BrS patients was 3.4 ± 1.7 cm 2 (range 1.5–7 cm 2 ). A significantly greater area of abnormal unipolar signals was identified (12.6 ± 4.6 cm 2 [range 7–22 cm 2 ], P : 0.001). Both bipolar and unipolar electroanatomical abnormalities were mainly located at the free wall of the RVOT. The mean RVOT activation time was significantly prolonged in BrS patients compared to control population (86.4 ± 16.5 vs. 63.4 ± 9.7 ms, P  < 0.001). Isochronal mapping demonstrated lines of conduction slowing within the RVOT in 8/10 BrS patients. Conclusion: Wide areas of endocardial unipolar voltage abnormalities that possibly reflect epicardial structural abnormalities are identified at the RVOT of BrS patients.